1988
DOI: 10.1093/sleep/11.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Apnea, Proteinuria, and Nephrotic Syndrome

Abstract: Renal abnormalities in patients with obstructive sleep apnea syndrome (OSAS) have not been previously described. Medical records of patients who had been evaluated for possible sleep apnea syndrome and had had complete polysomnograms and urinalyses were reviewed to determine the frequency of proteinuria. High-grade proteinuria (greater than or equal to 3+ on urinalysis) was found in 6 of the 34 patients with obstructive sleep apnea, but in none of 34 patients in a control group matched for sex, age, and weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
3

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 0 publications
0
25
0
3
Order By: Relevance
“…As already noted, several case reports and cross-sectional studies found a relation between sleep apnea and proteinuria [20,21,22,23,24], while others did not [44, 45]. Two reports restudied a small number of patients after treatment for SDB and found a reduction in proteinuria levels with no change in overall patient characteristics [20, 21]. One study in children assessed the presence of various proteins in urine samples of children with and without sleep apnea.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…As already noted, several case reports and cross-sectional studies found a relation between sleep apnea and proteinuria [20,21,22,23,24], while others did not [44, 45]. Two reports restudied a small number of patients after treatment for SDB and found a reduction in proteinuria levels with no change in overall patient characteristics [20, 21]. One study in children assessed the presence of various proteins in urine samples of children with and without sleep apnea.…”
Section: Discussionmentioning
confidence: 80%
“…It is therefore possible that SDB could further exacerbate the obesity-related renal injury. Indeed, several studies in adults reported a positive association between SDB and proteinuria [20,21,22,23,24]. To the best of our knowledge, this aspect has not been studied yet in obese children and adolescents.…”
Section: Introductionmentioning
confidence: 97%
“…Support for an association between hypoxia and development of progressive chronic kidney disease comes from numerous in-vitro and in-vivo studies of the effect of hypoxia on tubular and interstitial cells [3], while human physiology studies also demonstrate alterations in renal hemodynamics directly attributable to hypoxia [4], [5]. Although the Sleep Heart Health Study suggested an association between nocturnal hypoxia and risk of hypertension [6], reports on the effect of sleep disordered breathing on renal function are not consistent [7], [8], [9], [10], [11], [12], [13] and there are no studies examining loss of kidney function as the primary outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with OSAS (obstructive sleep apnoea syndrome) sometimes demonstrate proteinuria, which occasionally develops to the nephrotic stage and is associated with renal dysfunction [1][2][3][4][5][6][7][8]. Glomerular hypertrophy and/or focal segmental glomerulosclerosis are characteristic histological findings in biopsy studies of these patients [1][2][3]9].…”
Section: Introductionmentioning
confidence: 99%